THE CHROMOSPHERE-LIKE ENVELOPE OF THE VARIABLE STAR T TAU - Shpychka, I. V.; Virun, N. V. (Одеські астрономічні публікації, 2017)
The emission measure of the near-star chromosphere-like envelope of variable star T Tau with various mechanisms of radiation is computed. The normalization on the observed distribution of energy in continuum spectrum is carried out. The accretion disk and chromosphere models of the T Tau are discussed.